Mechanical and functional properties degradation mechanism of electron beam welded NiTi shape memory alloy. (April 2022) - Liu, Junpeng; Chen, Guoqing; Cao, Hui; Yin, Qianxing; Yu, Sen; Zhang, Binggang; Cao, Jian; Huang, Yongxian
Abstract: As advanced functional materials, NiTi shape memory alloys (NiTi SMAs), of which the welding reliability and functionality have always been the research hotspot, are widely used in aerospace and other fields. The existing research shows that the property of the welded joint is poor, as is expected from the welding defects such as porosities, cracks, unfavorable microstructure, and softening of heat affected zone. In this study, the microstructure of welded joint, fracture location, and martensite morphology was analyzed to explore the underlying causes of the deteriorated property of welded joint. The Ni50 Ti50 alloy plates were successfully joined by electron beam welding (EBW), and the mechanism of microstructure evolution was studied. The results showed that the center of the fusion zone was the weak zone, corresponding to the poor mechanical properties. Due to the formation of a 'crystallization line' at the interface of columnar grains, the brittle phase precipitation and grain boundary oxidation appeared. In addition, the deteriorated functional property of shape memory was attributable to the decrease in the number and size of lamellar martensite and the increase in dislocation density. Highlights: The shape memory effect of the fusion zone and the heat-affected zone was studied for the first time. The underlying reason for grain boundary weakening in NiTi alloy was put forward. The influence of the martensite phase and dislocation on the memory effect was revealed. The formation mechanism of the 'crystallization line' of NiTi SMAs was revealed.